Investigating SAR Insights into Royleanones for P-gp Modulation - Gabrielle Bangay; Vera M. S. Isca; Florencia Z. Brauning; Jelena Dinic; Milica Pesic; Bernardo Brito Palma; Daniel J. V. A. dos Santos; Ana M. Díaz-Lanza; Eduardo Borges de Melo; João Paulo Ataide Martins; Patrícia Rijo (Chemistry Proceedings)
Multidrug resistance (MDR) presents a significant challenge in modern pharmacotherapy, greatly diminishing the effectiveness of chemotherapeutic agents. A primary mechanism contributing to MDR is the overexpression of P-glycoprotein (P-gp), also known as MDR1, encoded by the ABCB1 gene, which hampers the success of cancer treatments. Plants from the Plectranthus genus (Lamiaceae) have been traditionally acknowledged for their diverse therapeutic applications. The principal diterpene from Plectranthus grandidentatus Gürke, 7α-acetoxy-6β-hydroxyroyleanone (Roy), has demonstrated anticancer properties against various cancer cell lines. Previously synthesized ester derivatives of Roy have shown improved binding affinity to P-gp. This study employs previously acquired in vitro data on the P-gp activity of Roy derivatives to develop a ligand-based pharmacophore model, highlighting critical features necessary for P-gp modulation. Utilizing these data, we predict the potential of five novel ester derivatives of Roy to modulate P-gp in vitro against resistant NCI-H460 cells. In silico structure–activity relationship (SAR) studies were conducted on 17 previously synthesized royleanone derivatives. A binary classification model was constructed, distinguishing inactive from active compounds, generating 11,016 molecular interaction field (MIF) descriptors from structures optimized at the DFT level. After variable reduction and selection, 12 descriptors were chosen, resulting in a model with two latent variables (LV), using only 34.14% of the encoded information for calibration (LV1: 26.82%; LV2: 7.32%). The activity prediction of new derivatives suggested that four of them have a high likelihood of activity, which will be validated in future in vitro biological assays.